LYUDMIL FERDINANDOV VAGALINSKI, Burnished pottery from the first century to the beginning of the seventh century AD from the region south of the lower Danube (Bulgaria), Sofia, NOUS Publishers Ltd., 2002, σσ. 200, 1 χάρτης, 49 πίν. (Στη βουλγαρική με παρά - Πούλου-Παπαδημητρίου, Ναταλία (Μακεδονικά, 2011)
no abstract